Mathematical Modelling of Drying Kinetics of Anonna Muricata L. (Soursop) Seeds Under Different Drying Conditions - Odunnayo, Olabinjo, Oyebola (Canadian Journal of Agriculture and Crops, 2020)
The seeds of soursop were dried to preserve the physical and physiological nature of the seeds. The thin layer drying performance of Anonna muricata (Soursop)seeds under three diverse drying techniques; open sun, heat pump and oven drying strategies at temperature of 40oC were assessed so as to foresee the best equation for the drying kinetics from thirteen (13) existing drying Mathematical models. Fresh samples of the seeds were gotten and dried at the same time under these drying strategies and weighed at regular interim until consistent weight was accomplished. The drying data; moisture loss and drying rate were gotten and changed to moisture ratio which was fitted to the thirteen mathematical models. The best fit model to portray the thin layer drying of Anonna muricata (Soursop) leaves was accomplished dependent on the model with the highest correlation coefficient (R2), and lowest reduced chi square (χ2) and root mean square error (RMSE). Two term models were the best and most appropriate in predicting drying kinetics of soursop seeds under the different drying methods of study. It had highest R2 of 0.9993, lowest Chi square of 0.000, and RMSE of 0.0047, highest R2 of 0.991, Chi square of 0.0003, and RMSE of 0.0157 and highest R2 of 0.9961, Chi square of 0.0085 and lowest RMSE of 0.0093 for open, oven and heat pump respectively It is featured that in the drying processes, the lesser the activation energy, the more prominent will be water diffusion inside the product.